Dichotomy “Own - Alien” in Discourse of Palestinian-Israeli Conflict from Point of View of Linguistic Imagology (on Material of Novels by Lynne Reid Banks “Broken Bridge” and Gloria Dubov Miklowitz “The Enemy Has a Face”) - S. D. Kamalova (Tsentr nauchnykh i obrazovatelnykh proektov, 2018)
The semantic opposition “own - alien” and its transformation into a dichotomy “own - other” is considered from the position of a new interdisciplinary scientific direction - linguistic imagology. The definition of a new sphere of scientific knowledge is given with reference to the few authors developing this direction. The study is based on the material of English-language works of art devoted to the Palestinian-Israeli conflict. The authors of the studied works represent the position of the Israeli side of the confrontation. The linguistic means of realization of mechanisms and products of linguistic imagology are analyzed, such as auto- and hetero-image, stereotype, mythologeme. The semantic series “other, alien, enemy” and their actualization in the considered works of art are investigated. On the basis of the analysis the tendency of consideration of the Israeli and Palestinian sides of the conflict is revealed through the prism of dichotomy “own - other,” instead of the opposition “own - alien,” indicating the desire of the authors of the studied works to identify the proximity of the two peoples, the possibility of their peaceful coexistence, as evidenced by linguistic analysis of language means. The transition of the opposite side of the conflict from the circle of “aliens” to the circle of “others” is achieved, in particular, by uniting Palestinian and Israeli characters against third forces, which is actualized through inclusive “ we ,” parallel structures, aphoristic statements and rhetorical exclamations about the need to end the hostilities. Based on the results of the study, it is assumed that the English-speaking authors are in favour of smoothing the contradictions, seeking to represent the parties of the conflict as related peoples, equally willing to live in peace.